The Cog-4 Subset of the National Institutes of Health Stroke Scale as a Measure of Cognition: Relationship with Baseline Factors and Functional Outcome after Stroke Using Data from the Virtual International Stroke Trials Archive. (26th March 2013) - Ankolekar, Sandeep; Renton, Cheryl; Sprigg, Nikola; Bath, Philip M. W.
Abstract : Background . Assessing poststroke cognitive impairment is complex. A subscale of the NIHSS, the Cog-4, has been proposed as a quick test of "cognitive impairment." but a study of its properties in a larger dataset is lacking. Methods . Data from 9, 147 patients with acute stroke from the VISTA archive was used to generate Cog-4 scores. The statistical properties of Cog-4, its relationship with baseline clinical characteristics, and other functional outcome measures at day 90 were assessed. Results . Mean age of patients was 69.2 years and 45.8%, were females. Day-90 Cog-4 was highly positively skewed (skewness 0.926). Patients with left hemispheric stroke had higher day-90 Cog-4 score (P < 0.001 ). Age, stroke severity, and previous stroke were significant predictors of Cog-4. Cog-4 was significantly correlated with dependency (modified Rankin Scale, r s = 0.512 ), and disability (Barthel Index, r s = − 0.493 ). Conclusions . The Cog-4 scale at day 90 cannot be considered a useful test of cognition since it only superficially measures cognition. It is heavily dependent on the side of stroke, is inevitably associated with functional outcome (being a subset of the NIHSS), and suffers from a profound "floor" effect. Specific and validated measures are more appropriate for the assessment of poststroke cognition than Cog-4.